Analysis of surface and subsurface layers after WEDM for Ti-6Al-4V with heat treatment. (February 2018) - Mouralova, K.; Kovar, J.; Klakurkova, L.; Blazik, P.; Kalivoda, M.; Kousal, P.
Abstract: The effective machining using the technology of wire electrical discharge machining (WEDM) is a compromise between cutting speed and resulting surface quality. The typical morphology of a machined surface using electrical erosion is characterised with numerous craters due to electrical discharges arising during the process of cutting. The study deals with the assessment of the influence of parameters of machine settings and material heat treatment on both quantitative and qualitative evaluations of craters on the surface of workpieces made of Ti-6Al-4V alloy. Using metallographic investigation, the diffusion subsurface phenomena occurring during the process of cutting on cross sections of preparations have been studied, and both qualitative and quantitative evaluations of the amount of electrode material stuck on the machined surface have been made. Diffusion processes occurring between the electrode and the cut material have been studied on cut surfaces as well as on cross sections using energy dispersive X-ray analysis (EDX).